Novel multidisciplinary hub-and-spoke tertiary service for the management of severe acute pancreatitis. Issue 1 (31st March 2021) - Nayar, Manu K; Bekkali, Noor L H; Bourne, David; Young, Sophie; Leeds, John S; Oppong, Kofi W; Logue, Jennifer L; Sen, Gourab; French, Jeremy J; Scott, John; Cressey, David; Pandanaboyana, Sanjay; et al.
Abstract : Objective: Severe acute pancreatitis (SAP) is associated with high mortality (15%–30%). Current guidelines recommend these patients are best managed in a multidisciplinary team setting. This study reports experience in the management of SAP within the UK's first reported hub-and-spoke pancreatitis network. Design: All patients with SAP referred to the remote care pancreatitis network between 2015 and 2017 were prospectively entered onto a database by a dedicated pancreatitis specialist nurse. Baseline characteristics, aetiology, intensive care unit (ICU) stay, interventions, complications, mortality and follow-up were analysed. Results: 285 patients admitted with SAP to secondary care hospitals during the study period were discussed with the dedicated pancreatitis specialist nurse and referred to the regional service. 83/285 patients (29%; 37 male) were transferred to the specialist centre mainly for drainage of infected pancreatic fluid collections (PFC) in 95% (n=79) of patients. Among the patients transferred; 29 (35%) patients developed multiorgan failure with an inpatient mortality of 14% (n=12/83). The median follow-up was 18.2 months (IQR=11.25–35.51). Multivariate analysis showed that transferred patients had statistically significant longer overall hospital stay (p<0.001) but less ICU stay (p<0.012). Conclusion: This hub-and-spoke model facilitates the management of the majority of patients with SAP in secondary care setting. 29% warranted transfer to our tertiary centre, predominantly for endoscopic drainage of PFCs. An evidence-based approach with a low threshold for transfer to tertiary care centre can result in lower mortality for SAP and fewer days in ICU.